Crystallite size induced crossover from paramagnetism to superparamagnetism in zinc ferrite nanoparticles. (October 2015) - Singh, Jitendra Pal; Gautam, Sanjeev; Srivastava, R.C.; Asokan, K.; Kanjilal, D.; Chae, Keun Hwa
Highlights: Synthesis of paramagnetic and superparamagnetic zinc ferrite. Fe 3+ ions along with the concomitant incomplete crystallization are responsible for superparamagnetic behavior. Increase of Fe–O bonds with crystallization. Abstract: Present work investigates the crossover from paramagnetism to superparamagnetism as a function of crystallite size in zinc ferrite nanoparticles using near edge X-ray absorption spectroscopy. Synthesized paramagnetic and superparamagnetic nanoparticles exhibit presence of Fe 2+ and Fe 3+ ions with dominant concentration of Fe 3+ ions. Fe L - and O K -edges spectra of paramagnetic nanoparticles consist of more intense spectral features compared to that of superparamagnetic nanoparticles. This reflects enhanced t 2 g and eg symmetry states of Fe–O hybridized states in paramagnetic nanoparticles induced by increased degree of crystallization.